‘Locating Viṣnupriyā in the Tradition’: Women, Devotion, and Bengali Vaiṣṇavism in Colonial Times - Dey, Santanu (Religions, 2020)
This article tries to map the gender element in Bengali Vaiṣṇavism by focusing on the evolution of the image of Viṣnupriyā, Caitanya’s second wife, as it progressed from the pre-colonial hagiographic tradition to the novel theorization of Gaura-Viṣnupriyā dual worship in the colonial period. It explores the varied ways in which certain segments of educated Bengali intelligentsia actively involved in reassessing Vaiṣṇavism in colonial times disseminated the idea that Viṣnupriyā was not just a symbol of unwavering devotion, of resolute penance, and (after Caitanya’s death) of ideal widowhood, but also deserved to be worshiped by Bengalis along with Caitanya as a divine couple. The article contends that while the ways of biographic imaging of Viṣnupriyā reveals the fissures and frictions within the colonial Vaiṣṇava reform process, it also highlights various continuities with pre-colonial strands of Vaiṣṇava thought.